2021
DOI: 10.1002/mp.15393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prediction and classification performances in different machine learning models for patient‐specific quality assurance of head‐and‐neck VMAT plans

Abstract: The purpose of this study is to evaluate the prediction and classification performances of the gamma passing rate (GPR) for different machine learning models and to select the best model for achieving machine learningbased patient-specific quality assurance (PSQA). Methods: The measurement verification of 356 head-and-neck volumetric modulated arc therapy plans was performed using a diode array phantom (Delta4 Phantom), and GPR values at 2%/2 mm with global normalization and 3%/2 mm with local normalization we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Sensitivity(Recall): the correct prediction ratio in the number of positive classes. See Equation (3). Specificity: the proportion of the number of negative classes that the wrong prediction was positive.…”
Section: Model Establishment and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity(Recall): the correct prediction ratio in the number of positive classes. See Equation (3). Specificity: the proportion of the number of negative classes that the wrong prediction was positive.…”
Section: Model Establishment and Evaluationmentioning
confidence: 99%
“…The conventional specific dosimetric verification based on the phantom which includes the dose recalculation, data transmission, set up, beam delivery, and γ analysis. It is not only increases the workload of the medical physicist, but also delays the first treatment of the patients [3]. To improve the efficiency and safety of IMRT implementation, the treatment plan complexity parameters were used to predict those plans that are not pass before treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence approaches have grown rapidly to improve conventional workflows of radiotherapy through automation 7–9 . In the case of the QA process, recently, several studies reported an auto PSQA process 10–40 . In general, they can be grouped into two categories: one for predicting the GPR 10–30 and the other for detecting errors 31–38 …”
Section: Introductionmentioning
confidence: 99%
“…In the case of the QA process, recently, several studies reported an auto PSQA process 10–40 . In general, they can be grouped into two categories: one for predicting the GPR 10–30 and the other for detecting errors 31–38 …”
Section: Introductionmentioning
confidence: 99%
“…An extensive line of research focused on developing non-learned treatment plan complexity metrics such as modulation complexity score, mean aperture displacement, or small aperture score and investigating their correlation with PSQA failure 14,15,16,17,18,19,20 . A large number of papers further extended these approaches by developing classical machine learning and deep learning models to predict the PSQA failure based on a vast array of the plan complexity metrics as well as other heuristic features 21,22,23,24,25,26,27,28 We compared the performance of our model with the results from two leading gradient boosted decision tree models in their CatBoost and XGBoost implementations 36,37 widely used for tabular data as well as to a non-learned complexity metric, mean MLC gap.…”
Section: Introductionmentioning
confidence: 99%